EVALUATION OF BONY EROSION IN PATIENTS WITH ALLERGIC FUNGAL RHINOSINUSITIS - BHATTI , S; ASHRAF , MA; IRFAN , A (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in Nishtar Medical Hospital & Bakhtawar Amin Hospital from January 2021 to January 2022 to evaluate CT findings of bone erosion and the implication of surgical treatment in patients with AFRS. The study was conducted on a total of 140 patients. All patients underwent sinus CT examination before the start of treatment. Experienced neuroradiologist examined CT characteristics of bone erosion. Data were recorded, including disease and bone erosion location, sinus expansion, and disease extension into neighboring anatomical spaces. Of 140 patients, 26 (18.5%) had radiographic evidence of bone erosion. 1 of the 26 patients had undergone previous endoscopic surgery. The ethmoid sinus was the most common site of bone erosion. The adjacent anatomic site which was affected most due to disease extension was the orbit. There was a significant association between bone expansion and expansion of frontal, sphenoid, ethmoid, and maxillary sinuses (P=.027). Bone erosion creates a route for disease progression in the intracranial cavity and orbit. It is not associated with fungal invasion and should be accurately differentiated from Sino nasal malignancy or invasive fungal sinusitis to avoid unnecessary invasive procedures.